2025 Business and Job Opportunities in Indonesia for Returning Migrant Workers from Hong Kong - Jumino; Mulyanto, Edi; Rahayu, Sri (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2026)
Hong Kong remains one of the primary destinations for PMI, especially in domestic and service sectors. However, many returning PMI struggle to achieve sustainable economic resilience due to limited understanding of entrepreneurship, low financial literacy, and restricted access to business capital. Meanwhile, Indonesia’s shift toward a digital economy, the rapid development of Micro, Small, and Medium Enterprises (MSMEs), and increasing regional investment present significant opportunities for PMI to pursue business and employment prospects upon their return. To support this transition, a Community Service Program (PKM) was delivered through online training focused on business and job opportunities in Indonesia in 2025, as well as financing mechanisms through banking and non-banking financial institutions. Conducted in collaboration with the Indonesia International School Hong Kong, the program involved 150 active PMI who are still working in Hong Kong and aimed to strengthen financial literacy and entrepreneurial readiness. Keywords: Migrant Workers, Remittances, Business Opportunities, Financial Literacy, Entrepreneurship